Genetic Recombination of the Mantle Color Pattern of Two Boring Giant Clam (Tridacna crocea) Strains - Wang, Junjie; Zhou, Zihua; Ma, Haitao; Li, Jun; Qin, Yanping; Wei, Jinkuan; Li, Xingyou; Liao, Qingliang; Li, Yunqing; Shi, Gongpengyang; Zhou, Yinyin; Zhang, Yuehuan; et al. (Frontiers in Marine Science, 2021)
The mantle color’s pattern of giant clams exhibit a rich polymorphism through four iridocytes according to the RGB principle display. The boring giant clam (Tridacna crocea) expresses brilliant mantle coloration in colors including blue, green, purple, gold, and orange. To evaluate the genetic laws driving these mantle color’s pattern, complete diallel crosses between two color strains, the blue strain (only blue iridocyte) and the yellow-green strain (yellow and green iridocytes), were conducted at an experimental station in Sanya, Hainan Island Province. Two intra-strain crosses (BB and YY) and two reciprocal inter-strain crosses (BY and YB) were carried out successfully three times using single to single mating. High fertilization rates and D larvae rate were observed in all the experimental groups, suggesting that there was no sperm-egg recognition barrier between the two’s strains. The size of the reciprocal hybrids were larger than the two pure strains during the grow out stage with a degree of heterosis. Additionally, the hybrids have a strong larval metamorphosis ability and a high survival rate when compared to the two pure strains. At one year, the mantle color’s pattern of pure strains is 100% stably inheritable, while the reciprocal hybrids both exhibited colorful patterns in blue, yellow, and green co-coloring, suggesting that there is a genetic recombination of mantle colors at the stable expression period. These results provided a basis to the theory of mantle color formation and their genetic separation law, and also suggests a practice on the genetic breeding of giant clams for aquaculture in coral reef area.